A Traffic Accident Causation Analysis Method Based on AHP-Apriori. (2016) - Xi, Jianfeng; Zhao, Zhonghao; Li, Wei; Wang, Quan
Abstract: The multivariate, layered nature of traffic accident analysis (TAA) determines that any TAA method must be categorized according to causational factors and encompass all four basic traffic elements, i.e. driver, vehicle, road and environment. The Analytic Hierarchy Process (AHP) is used to sequence accident causation factors according to their relative importance, with the purpose of singling out the most influential ones. The Apriori algorithm is then applied to analyze the degree of an accident or the level of influence. Through applications, the method proves itself capable of determining the type and severity of accidents caused by multiple factors. The method also demonstrates improvement in the accuracy and efficiency of calculation in dealing with large data samples.